2015
DOI: 10.1002/pros.22968
|View full text |Cite
|
Sign up to set email alerts
|

MiR200c targets IRS1 and suppresses prostate cancer cell growth

Abstract: Our results suggest that miR200c plays crucial roles in prostate cancer by post-transcriptional regulation of IRS1. The mir200c/IRS1 pathway may be a potential therapeutic target to prevent prostate cancer cell growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…In this study, we show that HIF-1α mRNA is a functionally relevant target of miR-199a-5p, the downregulation of which contributes to the oncogenic high level of HIF-1α in Pca [ 11 , 16 18 ], as well as tumor progression and unfavorable patient survival.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this study, we show that HIF-1α mRNA is a functionally relevant target of miR-199a-5p, the downregulation of which contributes to the oncogenic high level of HIF-1α in Pca [ 11 , 16 18 ], as well as tumor progression and unfavorable patient survival.…”
Section: Discussionmentioning
confidence: 98%
“…For example, underexpression of let-7c, miR-100, miR-145 and miR-218 in PCa was found to be associated with metastasis, and overexpression of miR-182 and miR-96 indicates a higher risk of progression [ 14 , 15 ]. In our previous reports, we demonstrated that downregulation of miR-145, miR-200c, and miR-199b is significantly associated with PCa progression; in contrast, we found hypoxia-inducible factor (HIF-1α), which may be suppressed by miR-199b, was overexpressed in PCa and inhibited apoptosis via BCL2-xL transactivation [ 11 , 16 18 ]. Expression of miR-199a-5p has been reported to be downregulated in certain tumors, including malignant testicular tumors, colorectal cancer and hepatocellular carcinoma, but upregulated in others, such as melanoma, gastric cancer and pancreatic adenocarcinoma [ 19 24 ], indicating tumor-type-specific regulatory mechanisms.…”
Section: Introductionmentioning
confidence: 93%
“…Moreover, several other genes present in the OncoScore lists, such as KLLN, LZTS1, BNIP3L, ING4 as well as MIR200C microRNA were recently implicated in the development of prostate cancer1415161718. Taken globally these data indicate that OncoScore is a useful prioritization tool for the annotation of copy-number abnormalities in human cancer.…”
Section: Resultsmentioning
confidence: 75%
“…Of them 74 had an OncoScore > 0 and 47 an OncoScore ≥ 21. A total of 8 cancer genes with an OncoScore above the 90 th percentile was identified (TNFRSF10B, [14][15][16][17][18] . Taken globally these data indicate that OncoScore is a useful prioritization tool for the annotation of copy-number abnormalities in human cancer.…”
Section: Oncoscore Analysis Of Large Structural Variationsmentioning
confidence: 99%